Continuous Venovenous Hemofiltration versus Continuous Venovenous Hemodiafiltration in Critically Ill Patients: A Retrospective Cohort Study from a Canadian Tertiary Centre - Farhan AlEnezi; Waleed Alhazzani; Jinhui Ma; Safug Alanazi; Mary Salib; Menat Attia; Lehana Thabane; Alison Fox-Robichaud (Canadian Respiratory Journal)
BACKGROUND: Studies comparing continuous renal replacement therapy modalities are lacking. Theoretically, continuous venovenous hemofiltration (CVVH) could be more effective than continuous venovenous hemodiafiltration (CVVHDF), and may be associated with fewer complications; however, there are no published data to support this hypothesis.